Thyroid hormones and carnitine in the second trimester negatively affect neonate birth weight: A prospective cohort study - Yang, Mengmeng; Sun, Man; Jiang, Chenyu; Wu, Qianqian; Jiang, Ying; Xu, Jian; Luo, Qiong (Frontiers in Endocrinology, 2023)
Background Maternal thyroid hormones and carnitine are reported to affect neonate birth weight during the second trimester, which is one of the most important markers for fetal growth and perinatal mortality and morbidity. Nevertheless, the effect of thyroid hormone and carnitine in the second trimester on birth weight has yet to be understood. Method This was a prospective cohort study with 844 subjects enrolled during the first trimester. Thyroid hormones, free carnitine (C0), neonate birth weight, as well as other related clinical and metabolic data were collected and assessed. Results Pre-pregnancy weight and body mass index (BMI) as well as neonate birth weight were significantly different among different free thyroxine (FT4) level groups. Maternal weight gain and neonate birth weight varied significantly when grouped by different thyroid-stimulating hormone (TSH) levels. There was a significantly positive correlation between C0 and TSH (r = 0.31), free triiodothyronine (FT3) (r = 0.37), and FT4 (r = 0.59) (all P < 0.001). In addition, a significantly negative influence was found between birth weight and TSH (r = −0.48, P = 0.028), so as C0 (r = −0.55, P < 0.001) and FT4 (r = −0.64, P < 0.001). Further assessment detected a stronger combined effect of C0 and FT4 (P < 0.001) and of C0 and FT3 (P = 0.022) on birth weight. Conclusion Maternal C0 and thyroid hormones are of great importance in neonate birth weight, and routine examination of C0 and thyroid hormones during the second trimester has a positive effect on the intervention of birth weight.